Difficulties in Translation from Turkish into Kazakh - Бaкытбекулы Ж.; Aбуовa A. (Journal of Oriental Studies, 2017)
This article is considered the common aspects and specific features of the Kazakh and Turkish languages. Discusses about confusing words specific to both languages, difficulties in translation from Turkish into Kazakh and inversely, as well as the common words in the dictionary of two languages. Gives some examples of the common words from the point of view of parts of speech, and identifies differences in their writing. Proves the fact of similarity of two languages not only at the level of words, but also at the level of phrases, sentences. Describes today’s interaction of two languages.